Effect of Livingstone Potato (Plectranthus esculentus N.E.Br) on Hepatic Glucose-6-Phosphophate Dehydrogenase Activity of Streptozotocin Induced Diabetic Rats - Ogbonnaya, Eleazu Chinedum (JOP. Journal of the Pancreas, 2014)
Context To determine the effect of Livingstone potato (Plectranthus esculentus N.E.Br) on hepatic G6PD in streptozotocin induced diabetic rats. Methods The G6PD activities in the liver homogenates of the rats and chemical analysis of the test feeds were determined using standard techniques. Results The diabetic control rats had significant elevation (P < 0.05) of their hepatic G6PD activities compared with the non-diabetic rats. Intake of the test feed by the diabetic rats of group 3, resulted in significant (P<0.05) amelioration of their hepatic G6PD activities in comparison with the diabetic control rats. Chemical analysis of the test feed revealed that it contained considerable amounts of tannins, saponins, alkaloids, antioxidants and their cyanide contents were below the toxic level for humans. Conclusion The study shows ameliorative potentials of Livingstone potato on the hepatic G6PD activity of diabetic rats which is attributed to its antioxidant/polyphenolic constituents. Image: Reducing power of test feed and standard quercetin.